2020
DOI: 10.1177/1534650120936771
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Foreign Accent Syndrome: A Single-Case Experimental Design

Abstract: Foreign accent syndrome (FAS) has historically been attributed to a neurological etiology. However, recent research has identified psychogenic causes of FAS, where patients present to health care services with medically unexplained FAS symptomology. Due to the rare nature of psychogenic FAS, there is currently no evidence-based psychological treatment for this syndrome. Although patients with psychogenic FAS do not meet the Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV) or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In this respect, for current patient, it is especially noteworthy that a large-scale epidemiological study has shown that childhood trauma does have a negative impact on conversion disorder therapy outcome 60 and it was mentioned earlier that patient claimed to not have benefited significantly from previous therapy. In a very recent paper by Birdsey and Millar, 61 CBT was also proposed to a woman suffering FAS on a psychogenic basis. Although CBT in that case study helped to reduce distress caused by the disorder as it did for this patient, it was not reported CBT helped to diminish the FAS and associated accent change itself.…”
Section: Language Mixing and Switchingmentioning
confidence: 99%
“…In this respect, for current patient, it is especially noteworthy that a large-scale epidemiological study has shown that childhood trauma does have a negative impact on conversion disorder therapy outcome 60 and it was mentioned earlier that patient claimed to not have benefited significantly from previous therapy. In a very recent paper by Birdsey and Millar, 61 CBT was also proposed to a woman suffering FAS on a psychogenic basis. Although CBT in that case study helped to reduce distress caused by the disorder as it did for this patient, it was not reported CBT helped to diminish the FAS and associated accent change itself.…”
Section: Language Mixing and Switchingmentioning
confidence: 99%